Washable and Flexible All Carbon Electrothermal Joule Heater for Electric Vehicles. Issue 7 (29th January 2023) - Weerathunga, Helapiyumi; Do, Thu Trang; Pham, Hong Duc; Jones, Robert; MacLeod, Jennifer; Kim, TaeYoung; Dubal, Deepak
Abstract: Amid the rapid development of electric vehicles, a flexible and waterproof radiant heater that can withstand repeated bending and washing is highly desirable. Herein, a freestanding, ultra‐flexible, and washable joule heater is constructed using a biocompatible poly(styrene‐isoprene‐styrene) (SIBS) polymer as binder and carbon black (CB) as heating material. By controlling the amount of CB and the thickness of the film, a minimum resistivity, and conductivity of 26 mΩ cm and 7.4 S cm −1, respectively, is achieved. Remarkably, the 28% CB/SIBS film can reach a maximum temperature of 201 °C while maintaining a stable temperature at 130 °C for repeated ON/OFF cycles. Time‐of‐flight secondary ion mass spectrometry of post‐mortem material analysis shows that a 1 h stability test at 130 °C has no sign of degradation and the films remain extremely stable. The films also show exceptional electrothermal heater performance after carrying out mechanical property tests such as bending (over 30°), repetitive bending (1000 cycles), twisting (two turns), and washing (soaked in distilled water for over 12 h). These outstanding heater performances incorporate extreme chemical stability and mechanical flexibility proposing that the CB/SIBS‐based electrothermal elements hold great potential for numerous practical applications, such as heating systems in electric vehicles and wearable electronics. Abstract : The uptake of electric vehicles (EVs) around the world is driving global demand for lithium‐ion batteries. The EVs of today suffer from key limitations in colder climates—the batteries discharge extremely quickly, resulting in significant reduced mileage. The present investigation develops an advanced carbon incorporated polymer matrix for washable, twistable, and stretchable electrothermal heaters with significantly less battery power consumption.